A Simple Synchronisation Method for Reproducing Tape-Recorded Profiles - Li, W. N.; Taylor Smith, D. (The International Hydrographic Review, 2015)
A simple method has been used to obtain synchronism in the reproduction of tape-recorded continuous reflexion profiling data for graphic display. By use of a 2-channel recording technique a reference signal, from a precision graphic recorder, can be simultaneously recorded with the acoustic data. This reference signal can then be used to govern the speed of the graphic recorder during play-back, totally eliminating any graphic distortion caused by tape speed deviation. The technique can be used with any relatively inexpensive tape recorder and can, consequently, broaden at low cost the scope of any sub-bottom profiling system or, for that matter, any profiling system which employs a precision graphic recorder.